A risk management framework for design science research - Baskerville, Richard; Pries-Heje, J.; Venable, John (IEEE Computer Society, 2011)
Design Science Research (DSR) is a complex form of research that combines very heterogeneous activities requiring different skills with more elaborate areas of risk to manage. As yet, there is little experience with managing risk in DSR or even identification of types of risks to be managed. This paper analyses DSR research activities and elaborates known principles and practices of risk management for DSR and develops a framework for identifying, assessing, prioritizing, and treating potential risks inherent to DSR. Potential users of the framework include experienced and espcially novice DSR researchers. The framework classifies six potential risk areas and enumerates specific key risks within each area. It includes risk assessment and treatment models. Finally the paper applies the framework to an ongojng DSR case study to provide initial evidence of its value and feasibility.